Kesiapan Perguruan Tinggi dalam Mencetak Sumber Daya Manusia di Sektor Energi Baru Terbarukan (Renewable Energy) - Ahmad Khulaemi (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Indonesia's energy mix target in 2025 is 23 %. While the achievement of the target in 2021 has only reached 11 %. Acceleration towards a 23% energy mix in 2025 requires the support of human resources (HR) in the field of Renewable Energy . These human resources are obtained from universities in Indonesia. This study aims to determine the curriculum and laboratories in universities in the field of renewable energy . The methodology of this research is descriptive qualitative with a simple survey approach using Microsoft form by random sampling. The number of respondents was 56 students from various public and private universities in Indonesia. The results showed that universities did not provide a special renewable energy curriculum and did not have a special renewable energy laboratory while student interest in learning renewable energy was very high. The conclusion of this study is that universities have not been able to support human resources in the field of renewable energy in terms of curriculum and laboratory infrastructure.